Review of JAEA’s Monte Carlo codes for nuclear reactor core analysis - Nagaya Yasunobu (EPJ Nuclear Sciences & Technologies)
Japan Atomic Energy Agency (JAEA) has been developing a general-purpose continuous-energy Monte Carlo code MVP for nuclear reactor core analysis. Recently improvements to MVP have been focused on the development of an advanced neutronics/thermal-hydraulics coupling code. JAEA has also developed a new Monte Carlo solver Solomon for criticality safety analysis. Solomon aims to calculate the criticality of fuel debris. This paper provides an overview of the capabilities and reviews recent applications of MVP and Solomon.